Chemical segregation and precipitation at anti-phase boundaries in thermoelectric Heusler-Fe2VAl. (September 2020) - Gomell, Leonie; Katnagallu, Shyam; Diack-Rasselio, Abou; Maier, Stefan; Perrière, Loïc; Scheu, Christina; Alleno, Eric; Gault, Baptiste
Abstract: Fe2 VAl exhibits promising properties for thermoelectric applications. Here, we investigated the microstructure of melt spun Fe2 VAl using electron microscopy, atom probe tomography and field ion microscopy. We observe platelet-shaped VCx Ny precipitates in the vicinity of antiphase boundaries (APB) oriented along the {100}-plane. The mean distance between these precipitates is (140 ± 40) nm. This distance is shorter than the mean free phonon path at room temperature in Fe2 VAl. Thus, these VCx Ny precipitates, combined with the APB may efficiently lower the thermal conductivity of the alloy. Graphical Abstract: Image, graphical abstract